Pengaruh Budaya Kaizen dan Horenso Terhadap Work Quality dan Work Perfomance Karyawan Di PT.Yamaha Musical Products Indonesia (YMPI) - Novita, Sarah Aulia; Wahono, Budi; Athia, Ita (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The purpose of this study was to determine "The Influence of Kaizen and Horenso Culture on Work Quality and Work Performance of Employees at PT. Yamaha Musical Products Indonesia (YMPI)." The quantitative approach is the methodological basis in this study, with data collection instruments in the form of questionnaires that apply a Likert measurement scale as a parameter for assessing the variables studied from 1-5. Involving 236 employees of the Woodwind Instrument-Final Assembly Department of PT. Yamaha Musical Products Indonesia. The technique used is purposive sampling used to collect data. Validity, reliability, normality, classical assumptions, multiple linear regression analysis, f test, t test, and determination coefficient (R2) tests were used to analyze the data. as data collection materials analyzed using IBM SPSS Statistical Software. The results of the study show that Kaizen and Horenso Culture simultaneously influence Work Quality and simultaneously show that Kaizen and Horenso Culture influence Work Performance. Meanwhile, the research results also show that Kaizen and Horenso Culture have a partial influence on Work Quality, and the research results show that Kaizen and Horenso Culture have a partial influence on Work Performance. Keywords: Kaize Culture, Horenso, Work Quality, Work Perfomance